2018
DOI: 10.13189/sa.2018.060101
|View full text |Cite
|
Sign up to set email alerts
|

The Inclusion of Students with Visual Impairment at Addis Ababa University, Ethiopia: Challenges and Prospects

Abstract: Following the introduction of Special Needs Education Program Strategy that Ethiopian government developed in 2006, all public HEIs have been required to implement inclusive education as a mandatory approach when educating students with impairment, including those who are visually impaired. However, the actual implementation of an inclusive approach is being challenged by the social, political and physical circumstances of higher education institutions. Therefore, this study aimed at examining the existing cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 23 publications
0
1
0
Order By: Relevance
“…Moreover, studies also identified various barriers that SWDs encounter during the teaching and learning processes at higher educational institutions. For instance, Tamerat (2019), Tiruneh (2019), Zelelew (2016), and Beyene et al (2023) identified several barriers affecting SWDs' academic success in higher education. These barriers include inaccessible physical environments, a lack of technological assistive devices, the absence of support units, poor awareness and preparation of staff, and a lack of clear and enabling inclusive policies.…”
Section: Disability and Inclusive Higher Educationmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, studies also identified various barriers that SWDs encounter during the teaching and learning processes at higher educational institutions. For instance, Tamerat (2019), Tiruneh (2019), Zelelew (2016), and Beyene et al (2023) identified several barriers affecting SWDs' academic success in higher education. These barriers include inaccessible physical environments, a lack of technological assistive devices, the absence of support units, poor awareness and preparation of staff, and a lack of clear and enabling inclusive policies.…”
Section: Disability and Inclusive Higher Educationmentioning
confidence: 99%
“…The main goal of those policies is to remove the barriers that prevent SWDs from fully participating in learning and social integration in higher education. The Ethiopian educational policies also emphasize the need to consider the needs of SWDs in educational settings (Zelelew, 2016). Conversely, Tiruneh (2019, p. 130) by referring the general Ethiopian inclusive education strategy, which governs all levels of education, concluded that the country inclusive education strategy appears to imply a less responsive learning environment for the inclusive higher education system.…”
Section: Disability and Inclusive Higher Educationmentioning
confidence: 99%
“…Students with visual impairment are the individuals who utilize their non-visual abilities as opposed to their visual abilities to learn. Students with visual Impairment (VI) indicate to those students who are lawfully blind or who use Braille and other non-visual instruments for their education (Zelelew, 2018).…”
Section: Introductionmentioning
confidence: 99%